Globalization of China’s petrochemicals industry - Sepulchre, Alain (Henry Stewart Talks, 2014)
Market dynamics, Playing fields, Competition, Feedstock, Pricing, Technology, Distribution, Comparative benchmark, Chinese national oil companies, Oil majors, ODI